A study on training and development of mid-level ophthalmic personnel (MLOP) in aravind eye hospitals (AEH) - SIVANANDAM, DR. PRASANNA; MS. RAHMATH NISHA A, (The journal of contemporary issues in business and government, 2020)
Aravind Eye hospital (AEH) is one of the self-funding healthcare delivery models where it creates value for its entire customer base, but captures the value only from a part of it by offering free-of-cost or at cost, high-quality service. It serves nearly 6,000 outpatients in the hospital every day like registration, vision test, preliminary exam, refraction, final exam, counseling and recommendation for surgery with the assistance of MLOP’s (Mid-level ophthalmic personnel) while contributing their services. The MLOP’s are played as the backbone (60% of the workforce) for supporting the physicians when providing the treatment. This study focuses on how the training and development programs are handled for MLOPs in AEH by considering various factors like Induction training, Self- transformation, Career growth, personal development, and organizational strategy in their training programs and how it effectively creates a positive impact in their development within the organization.